High-throughput high content quantification of HIV-1 viral infectious output - Teresa LuPone; Alexis Brantly; Oluwatofunmi Oteju; Stephanie M. Matt; Kaitlyn Runner; Emily A. Nickoloff-Bybel; Michael R. Nonnemacher; Peter J. Gaskill (PLoS ONE, 2026)
Infection with human immunodeficiency virus (HIV-1) remains a global health issue and still drives the development of significant pathology and various comorbidities. Antiretroviral therapy (ART) can effectively suppress viral replication but is often initiated months or years after initial infection, leaving a substantial period in which viral replication progresses unchecked. While ART suppresses HIV-1 replication, it does not prohibit the development of HIV-1-associated comorbidities, highlighting a lack of understanding in the connection between replication and HIV-1-associated pathogeneses. Further, a high percentage of all HIV-1 virions produced are non-infectious, and this proportion is much higher in ART-treated individuals, showing that despite inefficient viral replication, which becomes even less efficient with ART, HIV-1 is still able to drive disease. Thus, it is critical to better define HIV-1 replication dynamics to more effectively target different stages of the viral replication cycle in distinct cell populations. Here, we show a high-content imaging reporter assay that uses modified human osteosarcoma cells expressing HIV-1 receptors (GHOST cells) which fluoresce in response to HIV-1 infection. These cells have been previously used to assess HIV-1 infectivity and tropism, but this modified assay enables rapid evaluation of large numbers of samples with consistency and replicability, while also easily integrating into existing experimental pipelines that analyze p24 secretion in collected supernatants. This also allows for direct correlation between infectivity and p24 secretion, resulting in a deeper interrogation and more robust understanding of HIV-1 infection kinetics.